Anaesthetic management and peri-operative complications in dogs undergoing cardiac electrophysiology studies and radio-frequency catheter ablations - Wringe, Elliot; Boustead, Keagan; Iovanescu, Cristian; Barron, Lara; Downing, Fran (Frontiers in Veterinary Science, 2025)
BackgroundThe term supraventricular tachycardia (SVT) is used to describe tachydysrhythmias originating from structures at or above the atrioventricular (AV) node. While sustained SVT is uncommon in dogs, it is potentially a life-threatening arrhythmia. Electrophysiology (EP) studies and radio-frequency catheter ablation (RFCA) as a way of characterising the cause of SVT and as a definitive treatment are well described in humans and animals alike. In dogs, EP and RFCA are performed under general anaesthesia; anaesthetic management and associated complications associated with EP and RFCA in canine patients are poorly described.ObjectivesThis study aimed to describe anaesthetic management and evaluate peri-operative complications in dogs undergoing general anaesthesia for EP studies and RFCA for treatment of SVT at a single referral hospital.MethodsA retrospective review of the anaesthetic and hospital records of 44 dogs that underwent EP studies and RFCA at a single, referral hospital in the UK, between 2014 and 2024, was performed. Data collected included signalment, clinical findings, anaesthetic protocols, and parameters, as well as intraoperative and peri-operative complications.ResultsThe most common breed was the Labrador Retriever (47.7%), with a median age of 30 months (5–95 months). Anaesthetic management included premedication with a pure μ-opioid agonist (methadone), with or without acepromazine, induction using propofol or alfaxalone, and maintenance with isoflurane in oxygen and air via a circle rebreathing system. Intraoperative complications were recorded and included arrhythmias (97.7%), hypoventilation (84.1%), hypotension (65.1%), hypothermia (47.7%), and non-fatal cardiopulmonary arrest (CPA; 6.8%). Cardiovascular support was required in 75% of cases, including crystalloid boluses, colloids, anticholinergics, vasopressors, and inotropes. The most common arrhythmias were supraventricular tachycardia (97.7%), atrial fibrillation (13.9%), ventricular tachycardia (5.6%), ventricular fibrillation (2.8%), transient third-degree AV block (4.65%), and accelerated idioventricular rhythm (2.8%). Postoperative complications occurred in 22.7% of patients, most commonly mild gastrointestinal signs and arrhythmias. One death occurred 9 h postoperatively, resulting in an overall mortality of 2.27%.DiscussionEP studies and RFCA for SVT in dogs can be performed under general anaesthesia with a low incidence of major or catastrophic complications. Anaesthetic protocols using a μ-opioid agonist ± acepromazine, propofol induction, and isoflurane maintenance facilitated completion of procedures. Although intraoperative arrhythmias, hypotension, and hypoventilation were common, these events were manageable. Severe complications and peri-operative mortality were uncommon, and overall outcomes were favourable. Careful anaesthetic planning, consideration of the severity of underlying cardiac disease, and preparedness for cardiopulmonary emergencies are recommended to optimise patient management and outcomes.